1992
DOI: 10.2116/analsci.8.749
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Ion Complexation Behavior of Resins Prepared by a Novel Template Polymerization Technique

Abstract: A Cu2+-ion selective resin (resin A) was synthesized by a novel template polymerization technique, using oleic acid as a host monomer, divinylbenzene as a matrix-forming monomer and Cu2+ ion as a target molecule. The metal (Cu2+ and Cat) ion complexation equilibria of resin A together with a reference resin (resin B) studied potentiometrically indicate: l) rapid and reversible complexation reactions, and 2) a highly selective binding of resin A to Cu2+ ions. These properties show that Cu2+-ion selective caviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…23 Entre as vantagens da técnica incluem-se a cinética de ligação rápida e a facilidade em lidar com impressões de íons hidrofílicos. Assim, uma série de trabalhos têm sido publicados usando esta técnica, por exemplo, para os íons Co 2+ , Ni 2+ e Cu 2+ com microesferas impressas preparadas por polimerização em emulsão por sementes, que são obtidas utilizando estireno, divinilbenzeno, burilacilato e ácido metacrílico em água.…”
Section: Polímeros Orgânicos Impressos Com íOnsunclassified
“…23 Entre as vantagens da técnica incluem-se a cinética de ligação rápida e a facilidade em lidar com impressões de íons hidrofílicos. Assim, uma série de trabalhos têm sido publicados usando esta técnica, por exemplo, para os íons Co 2+ , Ni 2+ e Cu 2+ com microesferas impressas preparadas por polimerização em emulsão por sementes, que são obtidas utilizando estireno, divinilbenzeno, burilacilato e ácido metacrílico em água.…”
Section: Polímeros Orgânicos Impressos Com íOnsunclassified
“…Template Polymerization Method † Isamu FUJIWARA,* Mizuo MAEDA,** and Makoto TAKAGI*** already reported on the preparation of a templated resin by using this method for catching metal ions using oleic acid 8 and phosphoric acid 9,10 as functional surfactants. We also prepared the templated resin for ferrocyanide ion 11 using oleylamine as a surfactant monomer.…”
Section: Condensed-phosphate Imprinted Resins Prepared By a Surfacementioning
confidence: 99%
“…Therefore processes that give access to the large surface area of polymer colloids and yield materials that are useful in chromatography are attractive. Takagi et al [22][23][24][25] originally reported a metal imprinted polymer colloid. The method involves the use of a host surfactant that is a polymerizable surfactant with …”
Section: Polymer Colloidsmentioning
confidence: 99%